ANALISIS KORELASI PEMANFAATAN HASIL PERKEMBANGAN TEKNOLOGI INFORMASI TERHADAP TINGKAT KELULUSAN MAHASISWA PADA FAKULTAS EKONOMI UNIVERSITAS PAKUAN BOGOR - Satsangkaryon, Satsangkaryon (Universitas Pakuan, 2016)
ABSTRACTThe development of information technology (IT) is now very rapidly and their impact on student learning can be both positive and negative. From the data graduation in 2009/2010 known to students with graduation